INFORMATION AND GAME THEORETICAL APPROACH IN BUSINESS STRATEGY - Citra Nurhayati (InFestasi, 2007)
This paper will concentrates in explaining the applicationof game theoretical approach to gain information in the businessstrategy. The brief explanation about game and strategies areparticularly concern with applying the theoretical approach to the reallife. Auction, decision making process and e-commerce are identifyingthe role of the game in helping manager or the player to win thecompetition in the market.